Models of care for musculoskeletal health in Australia: now more than ever to drive evidence into health policy and practice - Briggs, Andrew; Towler, Simon; Speerin, R.; March, L. (CSIRO Publishing, 2014)
Musculoskeletal health conditions such as arthritis, osteoporosis and pain syndromes impart a profound socioeconomic burden worldwide, particularly in developed nations such as Australia. Despite the identified burden, substantial evidence-practice and care disparity gaps remain in service delivery and access that limit the potential for improved consumer outcomes and system efficiencies. Addressing these gaps requires a whole-of-sector response, supported by evidence-informed health policy. Models of care (MoCs) serve as a policy vehicle to embed evidence into health policy and guide practice through changes in service delivery systems and clinician behaviour. In Australia, MoCs for musculoskeletal health have been developed by networks of multidisciplinary stakeholders and are incrementally being implemented across health services, facilitated by dedicated policy units and clinical champions. A web of evidence is now emerging to support this approach to driving evidence into health policy and practice. Understanding the vernacular of MoCs and the development and implementation of MoCs is important to embracing this approach to health policy.